Bursaphelenchus hildegardae sp. n. (Nematoda: Parasitaphelenchidae) - a new species belonging to the ‘eggersi’ group (Journal of Nematode Morphology and Systematics, 2010)
Bursaphelenchus hildegardae sp. n. isolated from coniferous wood is described. The new species belongs to the ‘eggersi’ group. It is characterized by a body length of 911 (795-1000) ìm and 1032 (855-1335) ìm of males and females, respectively; slim body (a = 46); stylet 13 and 14 ìm long in males and females, respectively; lateral field with three lines; long postuterine branch; female tail with a finely rounded, strongly ventrally-bent terminus (c’ = 4.6); spicules 26 (23-28) ìm long and having a distinctly dorsally-bent condylus, and a dorso-ventrally visible terminal bursa. The new species differs from other species of the ‘eggersi’ group mainly by spicule shape, particularly by the thin hook-like condylus. It can be differentiated from B. eggersi and B. tusciae morphologically, by means of ITS-RFLP patterns and ITS1/2 rDNA sequences. The sequences distinguish the new species significantly from other Bursaphelenchus species.